Gaya Bahasa Pidato Mahmoud Abbas (Kajian Stilistika Perspektif Gorys Keraf) - Mia Mutmainah (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2022)
This study aims to examine the stylistic aspects of Mahmoud Abbas’ speech in the United Nations General Assembly 76th in September, 2021. The data of this research is collected from Mahmoud Abbas’ speech in the video uploaded in the UN Youtube channel. This is analytical descriptive research using Gorys Keraf’s theory. The result of this study is that the speech cointains numerous language style. The word preferences are based on the frequent words, specific words, associative words, and pronoun. The language style used in the speech is the style based on sentence structure and figure of speech. The results showed that Mahmoud Abbas' speech contained the predominance of ihtilal and Falasṫin. This dominance is measured based on statistics and shows a certain meaning effect. Mahmoud Abbas' speech was also dominated by Israeli-Palestinian word associations, special dictions, and variations of pronouns. The language style of Mahmoud Abbas' speech is also colored by figurative language style, namely rhetorical style, allegory, and satire. This style of language influences meaning.Keyword - Mahmoud Abbas, United Nations, Speech, Stylistic